Moving Mountains : How One Woman and Her Community Won Justice from Big Coal - Loeb, Penny (Book collections on Project MUSE., 2007)
In late 1994, wells in Pie, West Virginia, began to go dry, leaving many residents of the small coal-mining town without potable water. When local housewife Trish Bragg made a few phone calls in an effort to solve this problem, she had no idea that her inquiries would eventually lead to her becoming the named plaintiff in a major lawsuit, a summa cum laude college graduate, and a hero of her community. Moving Mountains recounts the struggle of Trish Bragg and other ordinary West Virginians for fair treatment by the coal companies that dominate the local economies of southern West Virginia. The.